Local consolidative therapy for oligometastatic patients with stage IV non-small cell lung cancer may improve survival, but unanswered questions remain - Pacheco, Jose M.; Moghanaki, Drew (Translational Lung Cancer Research; Vol 8, Supplement 4 (December 31, 2019): Translational Lung Cancer Research, 2019)
Oligometastatic disease refers to a limited number of metastatic sites that are either “synchronous” when presenting at the time of initial diagnosis or “metachronous” when arising following therapy of the primary tumor. It is hypothesized that the biology of oligometastatic tumors may be different than that of tumors with more widespread metastases (1-3). As such, treatment of oligometastatic sites with local consolidative therapy (LCT) is a topic of interest, and has been increasingly offered in clinical practice. While there is no single definition of this state, it is commonly defined as up to 3–5 sites of metastases (excluding the primary lesion) following induction systemic therapy (1-6).